2022
DOI: 10.1039/d2sc03928a
|View full text |Cite
|
Sign up to set email alerts
|

A rotaxane-based platform for tailoring the pharmacokinetics of cancer-targeted radiotracers

Abstract: Radiolabelled monoclonal antibodies (mAbs) are a cornerstone of molecular diagnostic imaging and targeted radioimmunotherapy in Nuclear Medicine, but one of the major challenges in the field is to identify ways...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…Recently, we demonstrated that functionalization of the β-CD macrocycle is a convenient way of introducing either a biologically active vector to target cancer biomarkers or a multidentate aza-macrocyclic chelate for complexation of radioactive metal ions. 63 These pilot experiments relied on the derivatization of nonfunctionalized β-CD at one of the seven primary hydroxyl groups of the glucopyranose units with, for example, a photochemically active aryl azide group (ArN 3 ). Although the photochemical bioconjugation approach allowed us to synthesize viable 68 Ga-and 89 Zr-rotaxane-based radiotracers for applications in positron emission tomography (PET) imaging in vivo, introducing alternative reactive handles would increase the chemical scope and versatility of functionalized rotaxane formation through cooperative capture synthesis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we demonstrated that functionalization of the β-CD macrocycle is a convenient way of introducing either a biologically active vector to target cancer biomarkers or a multidentate aza-macrocyclic chelate for complexation of radioactive metal ions. 63 These pilot experiments relied on the derivatization of nonfunctionalized β-CD at one of the seven primary hydroxyl groups of the glucopyranose units with, for example, a photochemically active aryl azide group (ArN 3 ). Although the photochemical bioconjugation approach allowed us to synthesize viable 68 Ga-and 89 Zr-rotaxane-based radiotracers for applications in positron emission tomography (PET) imaging in vivo, introducing alternative reactive handles would increase the chemical scope and versatility of functionalized rotaxane formation through cooperative capture synthesis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Formation of the 1 ⊃ β-CD molecular inclusion complex is a prerequisite for [4]rotaxane synthesis and is expected to occur rapidly and reversibly at room temperature, with the position of equilibrium favoring the complex formation. 63 The second part of the reaction pathway, involving a double CB [6]-accelerated click process, is likely to occur in a stepwise fashion (see the kinetic and computational sections below) with successful [4]rotaxane synthesis observed in <5 min when the reaction mixtures were heated to 70 °C. Importantly, and despite solubility issues with CB [6] (vide infra), the reaction generally proceeds smoothly in water.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] Within the range of intertwined compounds, rotaxanes are postulated as ideal candidates for the design of molecular machines, developing applications in a wide range of fields, [4][5][6] such as catalysis, [7][8][9][10][11][12][13][14] materials science [15][16][17][18][19][20][21][22][23][24] or medicinal chemistry. [25][26][27] Usually, the design of these structures seeks the stability of the mechanical bond, thus preventing the dissociation of the different components in order to carry out a specific function. However, as it occurs in many biological processes, in which the mechanical bond is temporarily formed to undertake a precise function (such as the biological molecular machine processive catalysts), sometimes the design of these molecules requires the rational incorporation of certain functionalities which allow the dethreading of the counterparts by applying different stimuli.…”
Section: Introductionmentioning
confidence: 99%